Accelerated hypofractionated active raster-scanned carbon ion radiotherapy (CIRT) for laryngeal malignancies: feasibility and safety - Akbaba, Sati; Uzun-Lang, Kristin; Held, Thomas; Bulut, Cem; Mattke, Matthias; Uhl, Matthias; Plinkert, Peter K.; Rieken, Stefan; Herfarth, Klaus; Debus, Jürgen; Adeberg, Sebastian (Cancers, 2018)
(1) Background: The authors present the first results of active raster-scanned carbon ion radiotherapy (CIRT) for radioresistant laryngeal malignancies regarding efficacy and toxicity. (2) Methods: 15 patients with laryngeal adenoid cystic carcinoma (ACC; n = 8; 53.3%) or chondrosarcoma (CS; n = 7; 46.7%) who underwent radiotherapy with carbon ions (C12) at the Heidelberg Ion Beam Therapy Center (HIT) between 2013 and 2018 were identified retrospectively and analyzed for local control (LC), overall survival (OS), and distant progression-free survival using the Kaplan–Meier method. CIRT was applied either alone (n = 7, 46.7%) or in combination with intensity modulated radiotherapy (IMRT) (n = 8, 53.3%). The toxicity was assessed according to the Common Toxicity Terminology Criteria for Adverse Events (CTCAE) v4.03. (3). Results: the median follow-up was 24 months (range 5–61 months). Overall, the therapy was tolerated very well. No grade >3 acute and chronic toxicity could be identified. The most reported acute grade 3 side effects were acute dysphagia (n = 2; 13%) and acute odynophagia (n = 3; 20%), making supportive nutrition via gastric tube (n = 2; 13.3%) and via high caloric drinks (n = 1; 6.7%) necessary due to swallowing problems (n = 4; 27%). Overall, chronic grade 3 toxicity in the form of chronic hoarseness occurred in 7% of the patients (n = 1; 7%). At the last follow-up, all the patients were alive. No local or locoregional recurrence could be identified. Only one patient with laryngeal ACC developed lung metastases three years after the first diagnosis. (4) Conclusions: the accelerated hypofractionated active raster-scanned carbon ion radiotherapy for radioresistant laryngeal malignancies is feasible in practice with excellent local control rates and moderate acute and late toxicity. Further follow-ups are necessary to evaluate the long-term clinical outcome.
Gesehen am 22.11.2018